2024
DOI: 10.3390/s24020713
|View full text |Cite
|
Sign up to set email alerts
|

Anomaly Detection IDS for Detecting DoS Attacks in IoT Networks Based on Machine Learning Algorithms

Esra Altulaihan,
Mohammed Amin Almaiah,
Ahmed Aljughaiman

Abstract: Widespread and ever-increasing cybersecurity attacks against Internet of Things (IoT) systems are causing a wide range of problems for individuals and organizations. The IoT is self-configuring and open, making it vulnerable to insider and outsider attacks. In the IoT, devices are designed to self-configure, enabling them to connect to networks autonomously without extensive manual configuration. By using various protocols, technologies, and automated processes, self-configuring IoT devices are able to seamles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…To improve cybersecurity in IoT systems, the study in [ 72 ] addresses how to use the IoTID20 dataset to identify and stop denial-of-service (DoS) assaults. To keep an eye out for DoS abnormalities in network data, the authors suggested implementing ML classification methods in an IDS.…”
Section: Machine Learning—iot Network Anomaly Detectionmentioning
confidence: 99%
“…To improve cybersecurity in IoT systems, the study in [ 72 ] addresses how to use the IoTID20 dataset to identify and stop denial-of-service (DoS) assaults. To keep an eye out for DoS abnormalities in network data, the authors suggested implementing ML classification methods in an IDS.…”
Section: Machine Learning—iot Network Anomaly Detectionmentioning
confidence: 99%
“…KNN is valuable for classification as it does not assume underlying data distributions, making it a non-parametric and lazy learning algorithm. Non-parametric statistics operate under the assumption that there is no predefined data distribution [23]. In addition, the KNN algorithm takes as input the k-nearest training samples in the feature space.…”
Section: K-nearest Neighbor (Knn)mentioning
confidence: 99%
“…The accuracy of this algorithm can be significantly enhanced by normalizing the training data [24]. Furthermore, in KNN, the critical factor is the number of nearest neighbors [23].…”
Section: K-nearest Neighbor (Knn)mentioning
confidence: 99%
See 2 more Smart Citations